2018
DOI: 10.1111/jcmm.13888
|View full text |Cite
|
Sign up to set email alerts
|

CircRUNX2 through has‐miR‐203 regulates RUNX2 to prevent osteoporosis

Abstract: ObjectiveWe aimed to discover the molecular mechanism of hsa_circ_0076694 (circRUNX2) on osteogenic differentiation. We also explored the interaction between circRUNX2, miR‐203 and RUNX2.MethodsClinical samples obtained from femoral neck fracture patients’ bone tissues were used to collect circRUNX2, miR‐203, and RUNX2 expression data, while their expression changes were observed in human bone mesenchymal stem cells (hBMSCs) during osteogenic differentiation. QRT‐PCR and Western blot were used to analyse level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 21 publications
(44 reference statements)
2
33
0
Order By: Relevance
“…RUNX2 is a bone specific transcription factor. It is an important sign of osteoblasts differentiation and the process of bone formation [38]. High expression of RUNX2 can activate the transcription of bone sialoprotein (BSP) and osteocalcin, thereby promoting the maturation of osteoblasts and bone formation [39].…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 is a bone specific transcription factor. It is an important sign of osteoblasts differentiation and the process of bone formation [38]. High expression of RUNX2 can activate the transcription of bone sialoprotein (BSP) and osteocalcin, thereby promoting the maturation of osteoblasts and bone formation [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that Runx2 might increase the responsiveness of osteogenic cells to mitogenic signals by activating GPR30 . Another more recent study demonstrated that antagonism of GPR30 hindered the mineralization of MC3T3‐E1 cells induced by psoralidin, a common osteoporosis treatment agent . Concordantly, our findings show that agonism of GPR30 by G1 significantly upregulated expression of Runx2, and in turn, increased osteoblastic differentiation of MC3T3‐E1 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, highly expressed circ-SFMBT2 was observed in gastric cancer tissues, and proved to participate in the pathogenesis of gastric cancer via sponging miR-182-5p [22]. To date, only a few pathogenic circRNAs were reported in osteoporosis, and RNA sequencing tools and bioinformatics analysis were not employed in these studies [23][24][25]. Here, we constructed ceRNA networks with differentially expressed circRNAs and mRNA from whole transcriptome sequencing data, as well as intermediate miRNAs predicted through bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%